In vivo effects of 1a,25(OH)2D3-glycosides from Solanum glaucophyllum leaves in mice and skeletal muscle cells - Irazoqui, Ana Paula (2020)
We have previously shown that Solanum glaucophyllum leaves extract (SGE) enriched with 1a,25(OH)2D3-glucosides exhibits at least equal or greater effects on early myoblast differentiation as synthetic 1a,25(OH)2D3 thus being an effective substitute to promote muscle growth. Recently, we reported the effects of SGE compared to synthetic 1a,25(OH)2D3 in the regulation of mitogen activated protein kinases (MAPKs), genes involved on the differentiation of murine skeletal muscle cells C2C12, and their role on myotube formation. Since MAP kinase phosphatases (MKPs) deficiency impairs skeletal muscle regeneration and exacerbates muscular dystrophy, we further studied the effects of SGE on MKP1 and MKP5 which function to specifically dephosphorylate and inactivate MAPKs. SGE did not statistically modified MKP-1 and MKP-5 protein levels although basal changes were observed. MKP-1 protein levels remained unchanged at 1, 24 and 48 hours and decreased at 6 and 72 hours. MKP-5 protein levels increased at differentiation onset (24-72 h). We found that SGE significantly induced biphasic changes in phosphatase activity, decreased at 1 and 24 hours (which correlates with the pro-differentiation cell arrest previously reported), and increased at 6 hours. We also investigated the effects of SGE on Akt-mTOR signaling during the differentiation phase. SGE, decreased Akt phosphorylation after 5-day and increased its phosphorylation after 7-day of treatment. However, SGE did not induced changes in mTOR phosphorylation during time (3-7-day). Following with this approach, we investigated in vivo effects of SGE on skeletal muscle function in mice. Results from the first in vivo pilot test, have evidenced that 2 mg SGE/kg BW for 30 days did not show statically significant differences in phosphorus, calcium and glucose parameters from SGE groups compared to control. However, SGE leads to an increase in soleus muscle VDR protein expression in line with a significant decrease in 25(OH)D3 in blood serum while lower SGE doses did not change biochemical parameters measured in serum or protein content in mice muscle. These results contribute to elucidate the mechanism of action of the herbal active form of vitamin D when used as substitute to promote muscle growth